Effects of propolis from Brazil and Bulgaria on Salmonella serovars - R. O. Orsi; J. M. Sforcin; S. R. C. Funari; A. Fernandes-JR.; P. Rodrigues; V. Bankova (Journal of Venomous Animals and Toxins including Tropical Diseases, 2007)
Propolis shows biological properties such as antibacterial action. This bee product has a complex chemical composition, which depends on the local flora where it is produced. Salmonella serovars are responsible for human diseases that range from localized gastroenteritis to systemic infections. The aim of the present study was to investigate the susceptibility of Salmonella strains, isolated from food and infectious processes, to the antibacterial action of Brazilian and Bulgarian propolis, as well as to determine the behavior of these bacteria, according to the incubation period, in medium plus propolis. Dilution of ethanolic extract of propolis in agar was the used method. Brazilian and Bulgarian propolis showed an antibacterial action against all Salmonella serovars. The minimal inhibitory concentrations (MIC) of propolis were similar, although they were collected in different geographic regions. Salmonella typhimurium, isolated from human infection, was more resistant to propolis than Salmonella enteritidis.